Melacak Makna “Dain” dalam Al-Quran Perspektif Analisis Semantik Toshihiko Izutsu dan Penerapannya dalam Platform Belanja Online - Mohammad Zainal Hamdy; Riski Gunawan (International Conference on Islamic Economic (ICIE), 2025)
In Islamic teachings, debt (Dain) is a permissible transaction, but it is mandatory to be careful in implementing and carrying it out so as not to fall into something that is prohibited by Islam, namely Riba. Researchers will examine and trace the concept of Dain in the Qur'an using Toshihiko Izutsu's semantic analysis. In addition, the concept of Dain in the Qur'an has it been implemented correctly in several online shopping platforms that implement loans or debts such as Shopee and Lazada. researchers use a qualitative approach and the method or type of research used by researchers is Library Research. The results show that in the Qur'an, the concept of "dayn" or debt is not just a financial transaction. The worldview offered by the Qur'an regarding debt is about how this obligation functions in a wider network of social relations, where aspects of justice, transparency, understanding, and moral responsibility are highly emphasized. And the paylater system can be in accordance with the concept of "dayn" (debt) in the Qur'an with several conditions: Justice, Transparency, No Riba, Leanness.